Pt concentration dependence of the interfacial Dzyaloshinskii–Moriya interaction, the Gilbert damping parameter and the magnetic anisotropy in Py/Cu1−xPtx systems. (26th November 2018) - Bouloussa, H; Ramaswamy, R; Roussigné, Y; Stashkevich, A; Yang, H; Belmeguenai, M; Chérif, S M
Abstract: Physical effects generated by spin–orbit coupling (SOC) are extremely appealing to numerous applications related to magnetic information processing and to the rapidly developing field of spin-orbitronics. In this paper we have investigated major tendencies in the behavior of three of them, namely the Gilbert damping constant, the magnetic anisotropy and the interfacial Dzyaloshinskii–Moriya interaction (iDMI), as a function of Pt concentration in Py (5 nm)/Cu1−x Ptx bilayers, using a combined experimental approach based on ferromagnetic resonance and Brillouin light scattering techniques. The Gilbert damping constant and the magnetic anisotropy demonstrate similar simultaneous growth with Pt concentration. The iDMI presents a very weak value until the Pt concentration is about x = 45% and then increases rapidly until full Pt concentration. Magnetic anisotropy and the damping factor are found to be linearly correlated. On the other hand, above x = 45%, the iDMI increases with respect to the damping factor, thus with magnetic anisotropy. These behaviors show that these physical phenomena are correlated and suggest that they are closely associated with SOC. Moreover, this work opens up the possibility of independent tuning of different SOC-related parameters to tailor-made values optimal for a specific application.